Cognitive Side Effects of Antiepileptic Drugs - J Gordon Millichap (Pediatric Neurology Briefs)
Available studies of the cognitive side effects of traditional and newer antiepileptic drugs (AEDs) are reviewed by researchers at Georgetown University Medical Center, Washington, DC.